The Virtual Da’wa Laboratory for Islamic Moderatism: Multi-Case Study of Walisongo TV and MBS FM - Adeni, Adeni; Hasanah, Silviatul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This paper aims to analyze the virtual da'wa laboratory of Walisongo TV (WTV) and MBS FM owned by the Faculty of Da’wa and Communication, UIN Walisongo Semarang in nurturing Islamic moderatism during Ramadan 2020 amid the Covid-19 Pandemic. This research is a qualitative study using the New Media and Religion approach from Cambpbell (2010) who stated that there are two important objects regarding online religion, namely the technical aspects of new media, and the non-technical aspects related to three things, namely the community, authority, and textual media. The study concludes that first, technically WTV and MBS uses new media such as WhatsApp, Instagram, YouTube, Jitsi.meet, and Zoom meeting for all activities, starting from the internal crew's coordination; communication between crews and da’i in discussing da’wa contents; videos taking process; production activities, to promotions and publications. Second, non-technically WTV and MBS FM provide the products in the form of recordings and LIVE (live broadcast). The products represent the Islamic moderate community behind the media authorized by Nadlatul Ulama (NU) da’wa ideology. Hence, media text broadcasted is framed by the jargon “Islam Rahmatan li al-‘Alamin” based on the classical Islamic texts (Kitab Kuning). This suggests that community, authority, and textual media have to be taken into account in forming a virtual moderate da’wa laboratory.